PERSEPSI APARATUR FUNGSIONAL TENTANG KEAHLIAN DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP PENCEGAHAN KECURANGAN (Studi Pada Kantor Inspektorat Daerah Kabupaten Konawe) - Awaluddin, Ishak; Inayatillah, Dyah Auliah (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTThis research aimed to knows functional apparatusâ perception about expertise and internal control system of government to the fraud prevention in Inspectorate of Konawe Regency. Population in this research are employees in Inspectorate of Konawe Regency who task participated of inspection and supervision and samples in this research using the census method. The method used in this research is descriptive analysis. The results showed that functional apparatusâ perceptions about expertise and internal control system of government to the fraud prevention in Inspectorate of Konawe Regency are very strong. High expertise must be owned by the functional apparatus and functional apparatus must have a good understanding of the internal control system ofÂ  government effectiveness in order to fraud prevent because the better internal control then the better also in preventing acts of fraud.Keywords :Â Â Â Â  Functional Apparatus, Expertise, Internal Control Systems of Government and Fraud Prevention.